Treatment of diabetes and heart failure: a paradigm shift for cardiologists?. (March 2019) - Brochu, Bradley; Chan, Michael
Abstract : Purpose of review: Diabetes is a well-recognized risk factor for the development of cardiovascular disease. In recent years, several new glucose-lowering drugs (GLD) have shown improvements in cardiovascular outcomes, renewing interest of cardiovascular specialists in diabetes management. Recent findings: Individual studies in the last 5 years have demonstrated the cardiovascular safety of certain dipeptidyl peptidase-4 inhibitors, glucagon-like peptide 1 agonists, and sodium glucose cotransporter 2 inhibitors. Recent meta-analyses have attempted to demonstrate class effects of these medications, but remain driven by several large studies. Other studies have used registry data to show improvements in cardiovascular outcomes in patients receiving new GLD compared with insulin therapy. The cardiovascular benefits of GLD are so attractive that these agents have been applied to patients without diabetes, though these studies have not borne a net clinical benefit in nondiabetic patients. Summary: An evolving body of literature now supports the safety profile of many new GLDs in patients at risk for cardiovascular disease. Several new agents have demonstrated improvements in cardiovascular outcomes and are now recommended as second-line agents after metformin in patients with cardiovascular disease. Video abstract: http://links.lww.com/HCO/A54 Abstract : Supplemental Digital Content is available in the text